2020
DOI: 10.1074/mcp.ra120.001983
|View full text |Cite
|
Sign up to set email alerts
|

Proteaphagy in Mammalian Cells Can Function Independent of ATG5/ATG7

Abstract: The degradation of intra- and extracellular proteins is essential in all cell types and mediated by two systems, the ubiquitin-proteasome system (UPS) and the autophagy-lysosome pathway. This study investigates the changes in autophagosomal and lysosomal proteomes upon inhibition of proteasomes by bortezomib (BTZ) or MG132. We find an increased abundance of more than 50 proteins in lysosomes of cells in which the proteasome is inhibited. Among those are dihydrofolate reductase (DHFR), β-Catenin and 3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For example, the (active or passive) sequestration of proteasomes in aggregates is considered a major contributor to the toxicity of amyloidogenic protein aggregates (e.g., in Huntington's disease), as it reduces the active pool of proteasomes available for global PQC [186]. Furthermore, a growing body of literature suggests that proteasomes are themselves substrates of spatial sequestration and clearance through selective autophagy (‘proteaphagy’) in response to a range of stresses, including proteasome inhibition [187–191]. A recent study [191] showed that inhibited 26S proteasomes are ubiquitylated with K63‐chains by CHIP/STUB1, sequestered in the aggresome via the HDAC6‐dynein route, and cleared by p62/SQSTM1‐mediated selective autophagy.…”
Section: Emerging Concepts In Alternative Pqcmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the (active or passive) sequestration of proteasomes in aggregates is considered a major contributor to the toxicity of amyloidogenic protein aggregates (e.g., in Huntington's disease), as it reduces the active pool of proteasomes available for global PQC [186]. Furthermore, a growing body of literature suggests that proteasomes are themselves substrates of spatial sequestration and clearance through selective autophagy (‘proteaphagy’) in response to a range of stresses, including proteasome inhibition [187–191]. A recent study [191] showed that inhibited 26S proteasomes are ubiquitylated with K63‐chains by CHIP/STUB1, sequestered in the aggresome via the HDAC6‐dynein route, and cleared by p62/SQSTM1‐mediated selective autophagy.…”
Section: Emerging Concepts In Alternative Pqcmentioning
confidence: 99%
“…It will be important to establish the degree of overlap between misfolded proteins and proteasomes through this alternative PQC route. A proteomic analysis of isolated lysosomes in proteasome inhibitor‐treated human HEK293 fibroblasts identified a strong enrichment in both proteasomal particles and misfolded proteasomal substrates [190]—although whether these were targeted there through the same route was not determined.…”
Section: Emerging Concepts In Alternative Pqcmentioning
confidence: 99%
“…When stressed for nitrogen, on the other hand, proteaphagy is induced (Marshall et al, 2015;Waite et al, 2015;Nemec et al, 2017). Similarly, in human cells, proteasomes have been reported to undergo proteaphagy in response to amino acid starvation or upon proteasome inhibition (Cohen-Kaplan et al, 2016;Choi et al, 2020;Goebel et al, 2020). Interestingly, cytoplasmic proteasomes appear to be substrates for proteaphagy upon amino acid deprivation while nuclear proteasomes undergo liquid-liquid phase separation (LLPS) (Uriarte et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the quantitative comparison of a crude preparation of mitochondria against purified mitochondria from ten different mouse tissues greatly contributed to the mitochondrial compendium, MitoCarta 36 . Subtractive proteomics has helped establish the protein inventories of peroxisomes [193][194][195][196] , autophagosomes 197 and lysosomes 198 . A landmark single-organelle spatial proteomics paper described the systematic study of the human centrosome using intensity-based, label-free protein correlation profiling of consecutive density gradient fractions 30 .…”
Section: Characterizing Organelle Proteomesmentioning
confidence: 99%